THE PREVALENCE OF ENTEROBACTERIACEAE INFECTIONS IN THE SURGERY DEPARTMENT OF TRA VINH GENERAL HOSPITAL (Vietnam Journal of Community Medicine, 2026)
Antibiotic resistance among Enterobacteriaceae has become a serious threat to human health. Therefore, studying the prevalence of Enterobacteriaceae infections is essentia, as it helps determine the level of infection caused by this bacterial family and thereby supports appropriate and effective antibiotic treatment strategies.Objective: To determine the prevalence of Enterobacteriaceae infections in the Surgery Department of Tra Vinh General Hospital.Methods: A descriptive cross-sectional study was conducted on 115 isolates obtained from clinical specimens of patients undergoing the treatment in the Surgery Department of Trà Vinh General Hospital from May 2024 to August 2024.Results: The highest infection rate was observed in patients aged 40–60 years (40%), followed by those over 60 years (36.5%). The infection rate of E. coli accounted for 68.7%, Klebsiella spp. for 13%, Enterobacter spp. for 8.7%, Proteus spp. for 3.5%, and other intestinal bacteria for 6.1%.Conclusion: It is necessary to raise patients’ awareness of adherence to wound care and personal hygiene procedures to prevent infections, as well as to closely monitor infection control practices and hospital infection prevention behaviors among healthcare workers to reduce infection rates during patient treatment.
Keywords: Bacteria, Infection rate, Enterobacteriaceae, Surgery Department, Tra Vinh General Hospital.